Trade policy reform in the East Asian transition economies - Martin, Will, 1953- 1953- (Policy research working paper, 2001)
There has been no single magic formula for the success of the East Asian transition economies (Cambodia, China, Lao People's Democratic Republic, and Vietnam), whose performance in export and income growth has been strikingly better than that of transition economies in Eastern Europe and the former Soviet Union. Most of the trade policy problems that remain in these East Asian economies appear to be the problems more of development than of transition